THE FUNCTIONAL AND BEHAVIORAL ASPECTS OF THE ORGANIZATION’S TECHNOLOGICAL TRANSFORMATION - Kabeer, Mohd Ahmed; Shrivastava, Manish (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Organizational culture is shaped by people, procedures, and technology, reflecting integrity, progress, future plans, social impact, and brand value. The digital era is transforming working methods, communication, and consumer value. However, implementing rapid cultural changes can be challenging and may lead to issues with employee trust, performance, and office politics. The introduction of technology in healthcare improves processes and products, aiming for overall improvement and enhancing customer care. This has led to the need for professional competency upgrades as employees deliver improved quality services, highlighting the importance of adapting to the digital era.